Experimental and numerical investigations of biogas vortex combustion - Khaleghi, Mostafa (SAGE Publications, 2015)
Low calorific value of biogas is one of the most important barriers of biogas development in industrial scale. Since biogas upgrading is complicated and not economic, various characteristics of pure biogas combustion have been experimented in recent years. In this paper, the characteristics of biogas flame structure and emissions in nonpremixed vortex combustion are studied experimentally and numerically. A lab-scale asymmetric chamber is employed as an industrial vortex combustor model and characteristics of biogas vortex combustion such as temperature distribution inside the chamber, the flame stability and the combustion emissions are investigated with respect to the various mole fraction of CO2 in the biogas content. The flame structure and emissions were recorded by changing the percentage of CO2 mole fraction in the biogas from 0 to 40% by volume. The results indicate that the stability of nonpremixed biogas combustion decreases when the rate of CO2 mole fraction increases in the fuel. The rate of both CO2 and NOx formation of nonpremixed combustion reduce monotonically when the rate of CO2 fraction increases in the biogas ingredients.